2020
DOI: 10.2196/19198
|View full text |Cite
|
Sign up to set email alerts
|

Client Satisfaction and Experience With Telepsychiatry: Development and Validation of a Survey Using Clinical Quality Domains

Abstract: Background Telepsychiatry is an increasingly used model of mental health care that connects patients with psychiatrists at a distance via videoconference. Telepsychiatry is an effective clinical intervention that improves access to quality care in regions with limited resources or in clinical situations where in-person care is unavailable. Objective This study aims to develop a validated survey tool to measure patient experience and satisfaction with te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 39 publications
3
20
1
Order By: Relevance
“…Our results are aligned with other surveys very recently validated based on quality of care domains [ 24 ], showing high levels of satisfaction with telepsychiatry services. Other recent studies in older [ 25 , 26 ] and younger [ 27 ] adults showed similar results, all in smaller samples.…”
Section: Discussionsupporting
confidence: 90%
“…Our results are aligned with other surveys very recently validated based on quality of care domains [ 24 ], showing high levels of satisfaction with telepsychiatry services. Other recent studies in older [ 25 , 26 ] and younger [ 27 ] adults showed similar results, all in smaller samples.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of positive patient and provider experiences with TMH during the COVID-19 pandemic, along with the preference for integrating TMH in the post-pandemic world, were consistent with emerging literature in the early course of the pandemic. ( Guinart et al, 2021 , 2020 ; Sasangohar et al, 2020 ; Serhal et al, 2020 ). General telehealth studies have found that both patients and providers have high levels of satisfaction with the use of telehealth and are willing to use it in the future, finding it to be comparable in quality of care delivery, with increased flexibility and lower cost ( Andrews et al, 2020 ; Malouff et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such results are supported by findings from similar surveys, demonstrating high levels of satisfaction across a range of telehealth and tele-rounding services, even in older patients who may be considered more digitally averse. 9,10 It may be, however, that the clinician-driven nature of the virtual review service allows for improved patient satisfaction in this age group, with further studies indicating comparable acceptability to younger adults. 11…”
Section: Principal Findingsmentioning
confidence: 99%